2021
DOI: 10.1080/23802359.2021.1987172
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome and phylogenetic analysis of Corydalis fangshanensis W.T. Wang ex S.Y. He (Papaveraceae)

Abstract: The complete chloroplast (cp) genome of Corydalis fangshanensis W.T. Wang ex S.Y. He, a Chinese endemic plant with limestone-specific distribution was first reported. The cp genome was circular in structure and 192,554 bp in length, consisting of a large single copy region (LSC, 98,393 bp), two inverted repeat regions (IRs, 42,263 bp), and a small single copy region (SSC, 9,635 bp). The overall GC content of the genome was 40.26%. It encoded 112 unique genes, including 78 protein-coding genes, 30 tRNA genes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Surprisingly, limited plastomes to date are available for Corydalis species. Except for the seven plastomes from our previous studies Wang, 2020, 2021;Yu et al, 2021;Huang et al, 2022), only one Corydalis plastome was formally and trustfully reported (Wu et al, 2020). This is not only in striking contrast to a species-rich genus with more than 500 species but also to the attraction they have for scientific interest.…”
Section: Introductionmentioning
confidence: 65%
“…Surprisingly, limited plastomes to date are available for Corydalis species. Except for the seven plastomes from our previous studies Wang, 2020, 2021;Yu et al, 2021;Huang et al, 2022), only one Corydalis plastome was formally and trustfully reported (Wu et al, 2020). This is not only in striking contrast to a species-rich genus with more than 500 species but also to the attraction they have for scientific interest.…”
Section: Introductionmentioning
confidence: 65%
“…The chloroplast genomes of 12 Corydalis spp. have been published to date, with most being published in China, where this genus is mainly distributed [16,23,[38][39][40][41]. In this study, we compared the chloroplast genome sequences of Corydalis spp.…”
Section: Introductionmentioning
confidence: 99%
“…and Lamprocapnos spp. have been analyzed in the subfamily Fumarioideae [16,18,23,[38][39][40][41]44]. Therefore, to explore the diverse genetic structures of Corydalis and its close relatives, we included F. officinalis in our analysis.…”
Section: Introductionmentioning
confidence: 99%